Electron Delocalization Is Not a Satisfactory Explanation for the Preference for Branching in the Alkanes. Issue 33 (18th July 2013) - Gronert, Scott
<x xml:space="preserve">Abstract</x> What are the factors that make branched alkanes more stable? A recent article suggested that greater electron delocalization is the key, but here it is argued that delocalization is just one of many factors, and that interactions of a more global nature, such as geminal interactions, make a better basis set for analyzing these systems.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>